Identification of Novel Cytotoxic Peptide KENPVLSLVNGMF from Marine Sponge Xestospongia testudinaria, with Characterization of Stability in Human Serum - Quah, Yixian; Mohd Ismail, Nor Ismaliza; Ooi, Jillian Lean Sim; Affendi, Yang Amri; Abd Manan, Fazilah; Wong, Fai Chu; Chai, Tsun Thai (Springer Verlag, 2018)
Resistance and side effects are common problems for anticancer drugs used in chemotherapy. Thus, continued research to discover novel and specific anticancer drugs is obligatory. Marine sponges hold great promise as a source of potent cytotoxic peptides with future applications in cancer treatments. This study aimed to purify and identify cytotoxic peptides from the protein hydrolysates of the giant barrel sponge Xestospongia testudinaria, guided by a cytotoxicity assay based on the human cervical cancer cell line (HeLa). Comparison among trypsin, chymotrypsin, papain and alcalase hydrolysates of X. testudinaria revealed papain hydrolysate (PH) to be the most active. PH was purified consecutively by membrane ultrafiltration, gel filtration chromatography, and reversed-phase high performance liquid chromatography (RP-HPLC). Following liquid chromatography-tandem mass spectrometric analysis, two peptides were identified from the most cytotoxic RP-HPLC fraction: KENPVLSLVNGMF and LLATIPKVGVFSILV. Between the two, only the synthetic peptide KENPVLSLVNGMF showed cytotoxicity toward HeLa cells in a dose-dependent manner. KENPVLSLVNGMF (EC50 0.67 mM) was 3.8-fold more cytotoxic compared with anticancer drug 5-fluorouracil (EC50 2.56 mM). Furthermore, KENPVLSLVNGMF show only marginal 5% cytotoxicity to Hek293, a non-cancerous, human embryonic kidney cell line, when tested at 0.67 mM. The half-life of the peptide was 3.2 ± 0.5 h in human serum in vitro, as revealed by RP-HPLC analyses. These results suggest that KENPVLSLVNGMF identified from X. testudinaria papain hydrolysate has potential applications as peptide lead in future development of potent and specific anticancer drugs.